2020
DOI: 10.3329/bmjk.v52i1-2.46148
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity pattern of diarrhoeal pathogens in under five children

Abstract: Background: Different bacterial enteropathogens are responsible for diarrhoea in children less than 5 years of age in Bangladesh. This study aimed to determine the antimicrobial sensitivity pattern of diarrhoeal pathogens that is necessary to know for the specific management of acute bacterial diarrhoea. Objectives: To find out the bacterial enteropathogens causing diarrhoea and their antimicrobial sensitivity pattern in under 5 children. Methodology: This was an observational cross sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…However, lower rates of resistance were recorded in Macedonia 42 and Korea, 43 Pakistan 21 Bangladesh. 45 The main reason could be due to inappropriate use of antibiotics in Ethiopia. 46 …”
Section: Discussionmentioning
confidence: 99%
“…However, lower rates of resistance were recorded in Macedonia 42 and Korea, 43 Pakistan 21 Bangladesh. 45 The main reason could be due to inappropriate use of antibiotics in Ethiopia. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Children are easily getting infected due to contaminated water and food as well as by contacting contaminated surfaces or animals that may carry certain bacteria like Salmonella spp. (16)(17)(18). Most positive cases were reported in summer-rainy seasons except in pus where the highest count was observed in late autumn.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, E. coli bacteria was accounted very frequently (53.04% in urine, 36.28% in blood, and 54.55% in stool samples) which relates to other studies like 31.4% in Cameroonian towns (11), 34.1% in Namibia (12) and 86% in Nepal (10) were detected in the specimen of urine. Likewise, E. coli is the most common etiology of diarrhea among children in Bangladesh as well as in other developing countries resembling India (44.2%) and Sudan (53.8%) (17). Even in a blood specimen, the count of E. coli was the highest (n=41, 36.28%) where Simkhada et al in 2016 described Salmonella Paratyphi A (n=26, 54.17%) as the leading etiological agent in blood-borne infections and E. coli is only 6.25% (n=3) (22).…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Pervin et al ( 2019 ) in Bangladesh, out of two hundred seventeen (217) diarrhoeal stools, ninety-seven (97) bacterial isolates were isolated. Among ninety-seven (97) culture-positive cases, the percentages of E. coli , Shigella spp., and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…were 51-52.58, 15-15.46, and 8-8.25%, respectively. Salmonella enteritidis was the utmost common serotype in Europe, Latin America, and Asia, accounting for 87%, 31%, and 38% of the clinical isolates, respectively (Pervin et al 2019 ). In another study, 126 Salmonella isolates dispersed among seven serotypes were shown to be multidrug-resistant, with high rates of AMR to lincomycin (100%), rifampicin (100%), sulfadiazine (93.7%), erythromycin (89.7%), ciprofloxacin (81.0%), and gentamicin (75.4%).…”
Section: Discussionmentioning
confidence: 99%